Bringing borders back into cross-border regional innovation systems: Functions and dynamics. (August 2022) - Cappellano, Francesco; Sohn, Christophe; Makkonen, Teemu; Kaisto, Virpi
International boundaries have been mainly considered as barriers in literature on the 'cross-border regional innovation system' (CBRIS), in line with their traditional understanding. In this paper, we underline that such a perspective presents limits, and argue in favour of an understanding of multidimensional borders that are subject to dynamic change over time. By mobilizing conceptualizations from the field of border studies, we examine the various functions of borders to explain the innovation-led development potential in cross-border regions. In this view, international borders can function as an interface, a marker of difference or a symbol, rather than a mere barrier that separates regions. Further, we suggest that these border functions are key factors in explaining the 'fluctuating' integration dynamics of regional innovation systems across the border. Mobilizing evidence from two case studies in European and North American contexts, the paper sheds light on the border as a potential resource for innovation and discusses implications for future research.